Response mechanism of ethanol-tolerant Saccharomyces cerevisiae strain ES-42 to increased ethanol during continuous ethanol fermentation - Xue-Xue Ji; Quan Zhang; Bai-Xue Yang; Qing-Ran Song; Zhao-Yong Sun; Cai-Yun Xie; Yue-Qin Tang (Microbial Cell Factories)
Abstract Background Continuous fermentation offers advantages in improving production efficiency and reducing costs, making it highly competitive for industrial ethanol production. A key requirement for Saccharomyces cerevisiae strains used in this process is their tolerance to high ethanol concentrations, which enables them to adapt to continuous fermentation conditions. To explore how yeast cells respond to varying levels of ethanol stress during fermentation, a two-month continuous fermentation was conducted. Cells were collected at different ethanol concentrations (from 60 g/L to 100 g/L) for comparative transcriptomic analysis. Results During continuous fermentation, as ethanol concentration increased, the expression of genes associated with cytoplasmic ribosomes, translation, and fatty acid biosynthesis progressively declined, while the expression of genes related to heat shock proteins (HSPs) and ubiquitin-mediated protein degradation gradually increased. Besides, cells exhibited distinct responses to varying ethanol concentrations. At lower ethanol concentrations (nearly 70 g/L), genes involved in mitochondrial ribosomes, oxidative phosphorylation, the tricarboxylic acid (TCA) cycle, antioxidant enzymes, ergosterol synthesis, and glycerol biosynthesis were specifically upregulated compared to those at 60 g/L. This suggests that cells enhanced respiratory energy production, ROS scavenging capacity, and the synthesis of ergosterol and glycerol to counteract stress. At relatively higher ethanol concentrations (nearly 80 g/L), genes involved in respiration and ergosterol synthesis were inhibited, while those associated with glycolysis and glycerol biosynthesis were notably upregulated. This suggests a metabolic shift from respiration towards enhanced glycerol synthesis. Interestingly, the longevity-regulating pathway seemed to play a pivotal role in mediating the cellular adaptations to different ethanol concentrations. Upon reaching an ethanol concentration of 100 g/L, the aforementioned metabolic activities were largely inhibited. Cells primarily focused on enhancing the clearance of denatured proteins to preserve cellular viability. Conclusions This study elucidated the mechanisms by which an ethanol-tolerant S. cerevisiae strain adapts to increasing ethanol concentrations during continuous fermentation. The findings suggest that the longevity-regulating pathway may play a critical role in adapting to varying ethanol stress by regulating mitochondrial respiration, glycerol synthesis, ergosterol synthesis, antioxidant enzyme, and HSPs. This work provides a novel and valuable understanding of the mechanisms that govern ethanol tolerance during continuous fermentation.